Effect of surfactant-induced competitive displacement of whey protein conjugated to acid- or alkali-extracted potato pectin on emulsion stability. (May 2021) - Murayama, Daiki; Rankin, Scott A.; Ikeda, Shinya
Abstract: Covalently linked protein–polysaccharide conjugate pre-adsorbed to the interface often shows more enhanced resistance to displacement induced by competitively adsorbing small molecule surfactant than the pure protein component. The objective of this study was to investigate the effect of surfactant-induced competitive displacement of whey protein–potato pectin conjugate pre-adsorbed to oil droplet surfaces on the stability of the oil-in-water emulsion. Potato pectin extracted in either an acidic or alkaline condition was conjugated to bovine milk whey protein using the Maillard reaction. The formation of covalent linkage between the protein and pectin moieties was confirmed using sodium dodecyl sulfate–polyacrylamide gel electrophoresis. Atomic force microscopy studies of the interfacial films of the Maillard conjugates formed on flat water surfaces revealed that the alkali-extracted potato pectin provided more enhanced resistance to surfactant-induced competitive displacement from the air–water interface than the acid-extracted potato pectin. These results indicate that galactan side chains having an ability to self-assemble and form network structures had been preserved to a larger degree during the alkali-extraction. Furthermore, the alkali-extracted potato pectin prevented coalescence-induced increases in the oil droplet diameter in the oil-in-water emulsions prepared using the Maillard conjugate as the emulsifier upon the addition of up to 38.7 mM of the Tween 20 surfactant while maintaining relatively high levels of the surface load of protein (>0.8 mg/m 2 ). The present results demonstrate that the molecular structure of the polysaccharide moiety of protein–polysaccharide conjugate has significant impacts on its resistance to competitive displacement and emulsion stability. Graphical abstract: Image 1 Highlights: Potato pectin was conjugated covalently to whey protein using the Maillard reaction. The conjugation decreased surface activities, increasing droplet sizes in emulsions. Conjugates resisted competitive displacement from oil droplet surfaces by surfactant. Conjugates prevented surfactant-induced coalescence probed by droplet size increases. Galactan side chains of potato pectin play an essential role in stabilizing emulsions.